Dexamethasone Decreases Mortality Rate in Broiler Infected with Infectious Bronchitis Disease - Hatim A. J. AL-Shwilly; Jabbar A A Al-Sa’aidi; Mohammed Mousa Atta (Institute of Medico-legal Publications Pvt Ltd, 2021)
To investigate the impact of dexamethazone (Dx) with or without spiramycin (Sp.) in controlling the mortalityrate of broiler farms infected with infectious bronchitis (IB), two experiments were conducted. In the firstpilot experiment, 750 broiler chicks (Ross) were divided into control (C) and two treated groups receivedDx and Sp (G1) or only Sp (G2), respectively. Second experiment was conducted on five selected broilerfarms (6000 chicks each), two farms were kept without treatment as a control, whereas other farms weretreated with a combination of Dx and Sp. All birds were vaccinated against Newcastle disease (ND), avianinfluenza (AI), infectious bronchitis (IB) and infectious bursa disease (IBD), and monitored throughoutthe experiment to detect any respiratory sings. The treatment protocol was started when respiratory singsappear. Blood samples were collected at day 5 of treatment from jugular vein and serum was to assessaspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) andto detect the antibody titer for the deferent vaccines by ELISA. The result showed significant decrease ofmortality rate in G1 group among experimental groups and insignificant differences of liver function testsand immune response to the vaccination against ND and AI. It can be concluded that using a combination ofdexamethasone and spiramycin has an efficient effect to protect broiler chicks against infectious bronchitisby decreasing the mortality rate with no immune suppression.